Large matrix polymer solar cells fabricated by low cost air-brush spray deposition - 陈征 邓振波 吕昭月 周茂杨 朱丽杰 殷月红 李熊 (Optoelectronics letters, 2015)
In this paper,a 64 mm×64 mm matrix polymer solar cell（PSC） was fabricated by air-brush spray deposition.Although the open-circuit voltage（Voc） and the fill factor（FF） both need to be improved,the efficiency of matrix PSCs still reaches about 1.82%,and especially the current density achieves nearly 20 m A/cm2.The results verify that air-brush spray deposition is a suitable method to prepare large area PSC devices,and the process we use in this paper can be easily transplanted to roll-to-roll production.